Contractor’s perspective toward construction delay in road projects / Nur Nadhirah Muda and Nurul Huda Muhamad - Muda, Nur Nadhirah; Muhamad, Nurul Huda (2020)
Delay in the construction projects occurs when the project is unable to be completed on time. It is a common issue and considered one of the most recurrent problems in the construction industry. Therefore, the aim of this study is to improve construction delay in road projects. Three objectives have been formulated, namely, to identify the main causes that contributed to the construction delay in road projects, to determine the effects of the main causes of construction delay and to recommend solutions to improve construction delay in road projects. To achieve aim of this study, questionnaires have been distributed to G7 contractors in Kuala Lumpur who involved in road projects. The collected data were analysed in descriptive analysis by using Statistical Package for Social Science (SPSS). There are four factors that contributed to the main causes of construction delay namely contractor, client, consultant and external factor. The finding identified thirteen solutions to improve construction delay in road construction projects. This study reveals the most effective solutions agreed by the respondent are proper project planning and scheduling by the contractor while from client group the most effective way to improve delays are speed up progress payment. Most of the respondents agreed that frequent inspection by the consultant may reduce construction delay in road projects and from external group contractor need to speed up in submission of permits to the local authorities are the most appropriate way to minimise delay.